Cyclin Dependent Kinase Inhibitors Differentially Modulate Synergistic Cytokine Responsiveness of Hematopoietic Progenitor Cells - Broxmeyer, Hal E. (Mary Ann Liebert, Inc., 2012)
Cyclin dependent kinase inhibitors (CDKIs) influence proliferation of hematopoietic progenitor cells (HPCs), but little is known of how they influence proliferative responsiveness of HPCs to colony stimulating factors (CSFs), alone and in combination with other hematopoietically active factors, such as the potent co-stimulating cytokine stem cell factor (SCF), or inhibition by myelosuppressive chemokines. Using mice with deletions in p18(INK4c), p21(CIP1/WAF1), or p27(KIP1) genes, and in mice with double gene deletions for either p18/p21 or p18/p27, we determined effects of absence of these CDKIs and their interactions on functional HPC numbers in vivo, and HPC proliferative responsiveness in vitro. There is a decrease in bone marrow HPC proliferation in p18(−/−) mice commensurate with decreased numbers of HPC, suggesting a positive role for p18 on HPC in vivo, similar to that for p21. These positive effects of p18 dominate negative effects of p27 gene deletion. Moreover, the CDKIs differentially regulate responsiveness of granulocyte macrophage (GM) progenitors to synergistic cell proliferation in response to GM-CSF plus SCF, which is considered important for normal hematopoiesis. Responsiveness of HPCs to inhibition by myelosuppressive chemokines is directly related to the capacity of HPCs to respond to synergistic stimulation, and their cell cycle status. P18(INK4c) gene deletion rescued the loss of chemokine suppression of synergistic proliferation due to deletion of p21(CIP1/WAF1). These findings underscore the complex interplay of cell cycle regulators in HPC, and demonstrate that loss of one can sometimes be compensated by loss of another CDKI in both, a pro- or anti-proliferative context.